2010
DOI: 10.1002/ccd.22435
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous closure of multiple defects of the atrial septum: Procedural results and long‐term follow‐up

Abstract: Percutaneous closure of multiple ASDs is feasible and associated with a good outcome. A thorough identification and analysis of morphological aspects are mandatory in order to select the appropriate device and the optimal strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 23 publications
1
48
1
3
Order By: Relevance
“…Data about the feasibility and efficacy of using transcatheter approach to close the multiple ASDs are limited [3][4][5][6][7][8]. Cao et al [3] and Butera [4] reported the clinical result of percutaneous closure of multiple ASDs and provided initial experience of device closure for this type of ASD.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Data about the feasibility and efficacy of using transcatheter approach to close the multiple ASDs are limited [3][4][5][6][7][8]. Cao et al [3] and Butera [4] reported the clinical result of percutaneous closure of multiple ASDs and provided initial experience of device closure for this type of ASD.…”
Section: Discussionmentioning
confidence: 97%
“…Presenting with various morphologies, those defects are often difficult to close via transcatheter approach in technical aspect [3,5,8]. Meanwhile, due to the special design of ASD occluder device, as for two or more ASDs with close distance (<7 mm) between each other, percutaneous closure using multiple devices is also not recommended due to potential interface between the devices [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cribriform ya da multipl atriyal septal defekte sahip hastalarda, perkütan kapatma ile hem kısa hem uzun dönemde başarılı sonuçlar bildiren çalışmalar mevcuttur 7 . Fakat perkütan kapatma işleminde, geniş ya da multipl defekte sahip olan hastalar ile 1'den fazla occluder device kullanılan hastalarda rezidüel shunt oranı daha fazladır 8 .…”
Section: Discussionunclassified
“…The devices might interfere with blood flow and even increase the risk of thrombosis. This, however, has not been apparent in follow-up studies, even after cessation of antiplatelet therapy [5]. In addition, the devices might cause erosion of important tissues, including the aortic root, atrioventricular valves, or atrial free walls.…”
Section: Multi-fenestrated Asdmentioning
confidence: 99%